Identifikasi Jamur Rizosfer Pada Tanaman Pisang Kepok (Musa paradisiaca L.) Yang Tumbuh Di Dataran Dan Perbukitan: Identification of Rhizosphere Fungi in Banana Kepok (Musa paradisiaca L.) Plants Growing In Plains and Hills - Ni’matuljannah Akhsan; Surya Sila; Jamilatul Huda (Universitas Widya Gama Mahakam, 2021)
Banana is a commodity that supports food security and is also an agribusiness commodity that is cultivated in almost all countries with tropical and subtropical climates. Currently, the productivity of bananas developed by the community is still very low. The productivity gap is due to improper cultivation techniques and high pest and disease-causing disturbances, especially by fungal attacks found in the rhizosphere of banana plants. The aim of the study was to identify the rhizosphere fungus on the kepok banana plant that grows in the plains and hills. This research was conducted at the Laboratory of Plant Diseases Pests, Faculty of Agriculture, Mulawarman University. This research was conducted by surveying and taking soil samples. Three samples were taken from each place, so the total number of samples was 6 samples. The results of the research on the rhizosphere of the kepok banana plant that grew in the plains were Trichoderma sp., Rhizopus sp., Beauveria sp., Penicillium sp. and Aspergillus sp. with an average population of 30 x 103 CFU/g and the hills found the fungus Pythium sp., Trichoderma sp., Colletotrichum sp. and Fusarium sp. population mean 23.6 x 103 CFU/g